Long-term effect of different cropping systems on physical quality of soil in North-western India - KAUR, TEJINDER; SINGH, K.B. (Journal of Soil and Water Conservation, 2026)
Soil physical quality is an important indicator of a good soil environment for plant growth with optimum aeration, water movement, and nutrient transformations. The puddling practices in rice (Oryza sativa L.) crop, degrades the physical quality of soil through destruction of soil structure, reduction of soil porosity, and formation of hardpan. Also, the other cereal-cereal crop rotations, intensive tillage, and removal of crop residues affect the soil physical parameters. So, ten cropping systems viz. rice-wheat (R-W), maize- wheat (M-W); basmati rice-wheat-cowpea green manure (Br-W-Cgm); maize-mustard/gm-cowpea gm (M-Ms/gm-Cgm); maize-potato-spring groundnut (M-Po-Sg); maize-peas-spring groundnut (M-P-Sg); maize+cowpea (fodder)-maize fodder-oats fodder-sathi maize fodder ((M+C)f-Mf-Of-Smf); sorghum multicut fodder-barseem fodder (Sf-Bf); maize (cobs/fodder)-potato-onion ((M(c/f)-Po-On); baby corn- potato-okra (Bc-Po-Ok) were studied during 2020-21 to assess their impact on physical quality of soil. Significantly higher soil pH in M-Po-Sg and higher aggregate associated carbon, porosity, maximum water holding capacity, saturated hydraulic conductivity (SHC) and soil moisture retention in M-Ms/ gm-Cgm were observed. ((M+C)f-Mf-Of-Smf) showed significantly higher soil organic carbon, mean weight diameter, and water stable aggregates (WSA) while the lowest was reported in R-W. The lowest soil electrical conductivity (EC) was observed in M-Ms/gm-Cgm and (M+C)f-Mf-Of-SMF. Significantly higher bulk density was reported in (R-W) while lowest in M-Ms/gm-Cgm. Soil quality index (SQI) was higher in M-Ms/gm-Cgm followed by (M+C)f-Mf-Of-Smf, Sf-Bf, while lowest in R-W. The order of overall contribution of selected indicators to the SQI was 36.5%, 29.0%, 25.0% and 9.5% by WSA, SHC, pH, and EC, respectively. It is concluded that inclusion of green manures/fodders/legumes in rotations with cereal crops could improve the physical quality of soil compared to cereal-cereal rotations.